Pharmacokinetics and Pharmacodynamics of Piperaquine in a Murine Malaria Model - Moore, Brioni R. (American Society for Microbiology (ASM), 2008)
Piperaquine (PQ) is an important partner in antimalarial treatment strategies. However, there is a paucity of detailed preclinical and pharmacokinetic data to link PQ serum concentrations and toxicity or efficacy. The aim of this study was to investigate the pharmacokinetics and pharmacodynamics of PQ in a murine malaria treatment model. The study comprised three arms. (i) PQ pharmacokinetic parameters were determined in healthy and malaria-infected mice (90 mg/kg PQ phosphate [PQP]). (ii) For determination of single-dose pharmacodynamics, Swiss mice were inoculated with Plasmodium berghei parasites and given PQP (10, 30, or 90 mg/kg intraperitoneally) at 2 to 5% starting parasitemia. After 60 days, the 90-mg/kg PQP group was reinoculated with P. berghei. (iii) Combination efficacy was investigated at doses of 10 mg/kg PQP and 30 mg/kg dihydroartemisinin (DHA). The median survival times were 4, 10, and 54 days for 0, 10, and 30 mg/kg PQP, respectively. All mice given 90 mg/kg PQP survived beyond 60 days, with a mean parasitemia of <1% before and after reinoculation. The nadir for DHA plus PQP was significantly lower (22-fold ± 12-fold) than the initial parasitemia for the individual drugs (DHA, 12-fold ± 5-fold; PQP, 13-fold ± 3-fold; P = 0.007 [analysis of variance]). The elimination half-lives of PQ in healthy and infected mice were 18 and 16 days, respectively, and the extrapolated residual PQ concentration at 60 days (<10 μg/liter) was ineffective at suppressing P. berghei infection. PQ has a potent antimalarial effect after single-dose treatment, and its efficacy was enhanced by combination with DHA.